Administrative guidance on submission of dossiers and assessment reports for the peer‐review of pesticide active substances. Issue 4 (8th April 2019) - ,
Abstract : This document provides guidance to applicants submitting dossiers for approval of pesticide active substances, and to Member States preparing assessment reports on active substances within the scope of Regulation (EC) No 1107/2009 and Commission Implementing Regulation (EU) No 844/2012 and its subsequent amendments. It describes the administrative requirements for the preparation and submission of the dossier to support an application for the approval, the amendment of approval or the renewal of an existing approval of a pesticide active substance. The procedure and the associated timelines for handling applications for approval, from their submission to the adoption and publication of the EFSA conclusion are also described. This document also provides additional guidance with the aim to enhance the quality of dossiers and assessment reports. It provides instructions, guidance and templates for both the applicant and Rapporteur Member State on how data should be presented in the dossier and in the assessment report. The document finally presents the different possibilities applicants have to interact with EFSA staff under this peer review process and the support initiatives available during the different stages of the application life‐cycle.